A multimodal model of analysis for the translation of songs from stage musicals - Carpi, Beatrice (Meta, 2020)
Song translation has only recently become an area of interest for research purposes, with the development of studies on opera, films, folk music, cover songs, and more. Not many scholars have researched stage musicals, even though songs play a fundamental role in this type of performance, conveying meaning via verbal, audio and visual semiotic resources.A few studies on song translation can be identified, such as Low’s (2003; 2005) Pentathlon Approach and Franzon’s (2005) functional approach. These models of translation offer valuable guidelines on how to treat the lyrics, but what is missing is a systematic and multimodal model of analysis that can be applied to the song in its entirety. Kaindl (2005; 2013) takes into consideration the multimodality of songs, but only focuses on popular music and opera. Acknowledging the lack of substantial research on the interaction between modes, which is typical of stage musicals, this paper focuses on the development of a model of analysis that considers the semiotic complexity of songs. A new approach based on themes will allow for a more holistic view of the song and of its content.